Unmet medical needs definition and incentives: stakeholders perspectives on the reform of the EU pharmaceutical legislation - Wens, Io; Claessens, Zilke; Vanneste, Alice; Barbier, Liese; Janssens, Rosanne; Huys, Isabelle (Frontiers in Medicine, 2025)
IntroductionThe 2020 pharmaceutical strategy for Europe stressed that rethinking regulatory policies to foster innovation in disease areas with unmet medical needs (UMN) is one of the European Commission’s (EC) priority areas. To understand stakeholders’ views regarding appropriate UMN criteria and incentives, the EC developed a survey and launched it for public consultation between September and December 2021. This study aims to assess stakeholders’ views on the policy revisions proposed by the EC, particularly those regarding the definition of UMN, its criteria and incentives and evaluate how stakeholders’ views are reflected in the proposed reform of the EU pharmaceutical legislation of 2023.MethodsThe public consultation survey comprised 14 questions including multiple-choice and open answer questions about the reform of the pharmaceutical legislation. A mixed-method analysis was conducted on publicly available data of stakeholders’ responses, including descriptive and quantitative statistics for multiple-choice questions and a qualitative thematic framework analysis for open answer questions. A subgroup analysis was performed to assess differences and similarities in stakeholders’ views, and results were compared with the proposed reform of the EU pharmaceutical legislation.ResultsA total of 478 participants completed the survey consisting of 36% industry, 19% end-users, 17% healthcare providers, 7.5% researchers and 7.5% public bodies. All stakeholder groups favored including “absence of satisfactory authorized treatment” and “disease seriousness” as defining criteria for UMN. However, stakeholders disagreed on including the criterion “lack of access for patients,” with public bodies and industry being less in favour. Industry favored maintaining or having additional incentives like transferable exclusivity vouchers on top of current intellectual property rights to foster innovation. In contrast, other stakeholders supported alternative proposals, namely enhancing the use of scientific advice and implementing expediting measures for regulatory evaluation of medicines targeting UMN.ConclusionStakeholders agreed on including availability of alternatives and disease seriousness in the UMN definition but highlighted its ambiguity. Industry participants supported additional incentives like transferable exclusivity vouchers, whereas others preferred scientific and regulatory support. These findings underscore the need for further discussion on UMN criteria and incentives to stimulate innovation while ensuring patient-centric outcomes and equitable access to medicines across Europe.